Copper-based hybrid nanosystems for external stimuli mediated cancer therapy - Jana, Deblin (Nanyang Technological University, 2021)
Copper is one of the most widely used elements among the transition metal group owing to the flexible oxidation state, abundance, and interesting properties. Copper-based compounds have garnered interest as potential therapeutic moieties because of their photoactivation and Fenton-like catalyst properties. Still, it is challenging to selectively deliver and accumulate such therapeutic agents in the targeted pathological regions and avoid undesirable side effects. Recently, developing novel copper-based hybrid nanosystems to overcome the abovementioned challenges and facilitate tumor microenvironment-activated therapy has been of wide interest. Particularly, delivering copper-based compounds in their nanoparticle forms takes benefit of the enhanced permeability and retention effect for tumor-specific accumulation. Utilization of external stimuli to activate such nanomaterials in the tumor region can offer additional tumor ablation efficacy with fewer side effects. Therefore, there is growing attention to the construction of copper-based smart nanosystems for effective cancer treatment. Focusing on different high-yield, straightforward, and reproducible synthetic approaches, this dissertation highlights diverse paradigms to fabricate copper-based hybrid nanosystems that can be stimulated by exogenous factors to augment the therapeutic efficacy in vitro and in vivo. Firstly, Chapter 1 encompasses the literature review of nanomedicine, with the focus on copper-based nanotherapeutic agents. The current trends and limitations of nanotechnology in cancer treatment are first introduced, and the strategies to fabricate ideal drug delivery systems are highlighted. Next, different therapeutic strategies for inorganic nanomedicines are discussed briefly. In the later part of this chapter, a synopsis of the recent progress in copper-based nanomedicines and their hybrid counterparts is illustrated and exemplified with recent literature. Towards the end of this chapter, we discuss the research gaps and present the summary of this dissertation. Following this, in Chapter 2, we demonstrate how electrostatic interaction strategies can be harnessed to conjugate inorganic photosensitizer nanosheets with copper-based nanodots to produce a hybrid nanoconjugate. Importantly, the interaction of two semiconductor-like entities can modulate the electronic properties of the nanoconjugate giving rise to enhanced and synergistic photodynamic-photothermal therapy. Utilization of such biocompatible nanoconjugates can show admirable in vitro and in vivo therapeutic efficacy. To capitalize on the therapeutic efficacy and reduce the toxicity towards healthy cells, tumor microenvironment- and external stimuli-responsive nanosystems are preferred over widely used entities. Hence, in Chapter 3, a metallic glass-type trimetallic nanodot, with copper as an integral component, is reported. Notably, activation ability by both light and ultrasound renders the nanodots amplified chemodynamic properties and consequent therapeutic performance in vitro and in vivo. Lastly, we explored the use of copper in a hybrid carbon-based nanostructure to exhibit multimodal therapy, bypassing complex design strategies. In Chapter 4, we describe how copper can be incorporated in situ as a therapeutic moiety in the backbone of carbon dot, acting primarily as a sonosensitizer. The meticulously designed nanosystem got activated in the tumor microenvironment and generated multiple reactive oxygen species on low dose ultrasound irradiation, inducing apoptosis of cancer cells in vitro and in vivo. Chapter 5 concludes the therapeutic utilization of different copper-based hybrid nanostructures. The investigations in this dissertation provide an encouraging outlook for the utilization of copper-based nanosystems in cancer treatments in the future.